Bank competition in Africa : three essays - (:unkn) unknown (My University, 2014)
This thesis is concerned with the role of interbank competition in Africa. During the past decade, African banking systems have witnessed profound changes in their structure with some implications on the level of competition. Although the traditional view argues that intensified competition encourages banks to increase the supply of funds and improves banks management, a more pessimistic view sustains that competition can be detrimental for efficiency, inclusion and stability of banking sectors, especially in opaque markets. The aim of this dissertation is therefore to shed a new light on this debate in the context of Africa by offering three empirical contributions. The first part of this thesis provides an overview of financial systems in sub-Saharan Africa and motivates the purpose of this dissertation. A review of the literature on the consequences of competition in banking is presented in Chapter 3. The different measures of competition in banking are discussed in Chapter 4. The three following chapters focus on the original contributions of this dissertation. Chapter 5 evaluates the evolution of bank competition over the last decade in African countries using a sample of West African banks. The findings, based on different measures of competition, show an increase of competition over the past decade. Chapter 6 investigates the relationship between market power and efficiency. Empirical results document that banks with more market power are able to reduce costs but do no better at maximizing profits than banks with less market power. In Chapter 7, the complex relation ship between credit availability and competition is analyzed using a large sample of 70 developing countries. Findings show that firms located in countries with competitive banking markets have a significantly lower probability to be credit constrained. Results show that competition not only leads to less severe loan approval decisions but also reduces borrowers' discouragement. The
Keywords: African Research